Cyclin Y inhibits plasticity-induced AMPA receptor exocytosis and LTP - Cho, Eunsil; Kim, Dong-Hyun; Hur, Young-Na; Whitcomb, Daniel J.; Regan, Philip; Hong, Jung-Hwa; Kim, Hanna; Suh, Young Ho; Cho, Kwangwook; Park, Mikyoung (NATURE PUBLISHING GROUP, 2015)
Cyclin Y (CCNY) is a member of the cyclin protein family, known to regulate cell division in proliferating cells. Interestingly, CCNY is expressed in neurons that do not undergo cell division. Here, we report that CCNY negatively regulates long-term potentiation (LTP) of synaptic strength through inhibition of AMPA receptor trafficking. CCNY is enriched in postsynaptic fractions from rat forebrain and is localized adjacent to postsynaptic sites in dendritic spines in rat hippocampal neurons. Using live-cell imaging of a pH-sensitive AMPA receptor, we found that during LTP-inducing stimulation, CCNY inhibits AMPA receptor exocytosis in dendritic spines. Furthermore, CCNY abolishes LTP in hippocampal slices. Taken together, our findings demonstrate that CCNY inhibits plasticity-induced AMPA receptor delivery to synapses and thereby blocks LTP, identifying a novel function for CCNY in post-mitotic cells.
Keywords: LONG-TERM POTENTIATION; SYNAPTIC PLASTICITY; DENDRITIC SPINES; GLUR1 SUBUNIT; CELL-CYCLE; RECYCLING ENDOSOMES; PHOSPHORYLATION SITES; CONSERVED CYCLIN; SILENT SYNAPSES; MYOSIN VB